Analysis of the Impact of Remuneration, Supervision, and Work Discipline on Employee Performance Improvement at the North Labuhanbatu Regency Education Office - Mangunsong, Junita Apriani; Zulyaden, Ahmad; Fatia, Debi; Nasution, Elinasari; Yusrita, Yusrita (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the influence of remuneration, supervision, and work discipline on employee performance at the North Labuhanbatu Regency Education Office. The research method used a quantitative approach with a survey technique through a questionnaire to 132 employees. The results of multiple linear regression analysis show that these three variables have a positive and significant effect on employee performance, with work discipline having the most dominant influence. The coefficient of determination (R²) of 65.2% indicates that remuneration, supervision, and work discipline together explain employee performance. In conclusion, improving employee performance can be achieved through fair remuneration policies, effective supervision, and strong enforcement of work discipline.